Improving the robustness of IoT-powered smart city applications through service-reliant application authentication technique - Jamil Alsayaydeh, Jamil Abedalrahim; Irianto; Ali, Mohanad Faeq; Mohammed Al-Andoli, Mohammed Nasser; Herawan, Safarudin Gazali (Institute of Electrical and Electronics Engineers Inc., 2024)
In applications related to smart cities, the Internet of Things (IoT) promotes service scalability regardless of variations in user density. Many customers require several safety procedures to supply reliable and effective application services. Undependable user identity was the cause of the current case of Permanent Denial of Service (PDoS). The article discusses service-dependent application authentication (SRAA), a defense against PDoS attacks, in the context of smart cities. This authentication method uses the controlled access distribution mechanism to provide application security. The user application's link connectivity and synchronization capabilities with the user device are used in the monitored access distribution. Backpropagation (BP) learning is used to find errors in the user device, implementation, and verification connections. BP learning minimizes the given weights using the anomaly learned from the initial access distribution phase. The anomaly has been identified in order of earlier training eras to enable coordinated authorization for the distributed services. PDoS causes fewer weights to become disconnected from the service, diminishing the number of service failures for linked devices. The experimental findings have been implemented, and the suggested SRAA model lowers computation overhead by 18.14% and false rate by 10.96%, access success by 9.07%, authenticating duration by 15.38% and synchronization failure by 8.94% compared to other existing models.